Cerebral Microbleeds and Cortical Superficial Siderosis in Patients Presenting With Minor Cerebrovascular Events. Issue 9 (September 2016) - Zerna, Charlotte; Modi, Jayesh; Bilston, Lisa; Shoamanesh, Ashkan; Coutts, Shelagh B.; Smith, Eric E.
Abstract : Background and Purpose—: Transient focal neurological episodes occur in cerebral amyloid angiopathy (CAA) and can mimic transient ischemic attack (TIA). Risk factors and outcomes of minor ischemic stroke or TIA might differ in patients with and without cerebral microbleeds (CMBs), including CAA-consistent lobar CMB. Methods—: Baseline magnetic resonance imaging (MRI) was analyzed for CMBs and cortical superficial siderosis in 416 patients in the prospective computed tomography and MRI in the CATCH study (Triage of TIA and Minor Cerebrovascular Events to Identify High Risk Patients). Clinical symptoms, baseline characteristics, recurrence, and 90-day modified Rankin Scale were prospectively collected. MRI white-matter hyperintensity was measured using the Fazekas scale. Results—: CMBs were detected in 65 (15.6%) and cortical superficial siderosis in 11 patients (2.6%). Lobar CMBs were present in 49 (11.8%). In multivariable logistic regression adjusted for risk factors and age, subcortical Fazekas score was associated with lobar CMB (odds ratio, 2.07; 95% confidence interval, 1.23–3.48; P =0.006). Forty-two patients (10.1%) had lobar-only CMBs with or without cortical superficial siderosis consistent with modified Boston criteria for possible/probable CAA. The possible/probable CAA pattern was not predictive of recurrent TIA (odds ratio, 0.42; 95% confidence interval, 0.05–3.31; P =0.41), stroke (odds ratio, 1.24; 95% confidence interval, 0.26–5.99; P =0.79), or 90-day modified Rankin Scale score ≥2 (odds ratio, 1.38; 95% confidence interval, 0.62–3.07; P =0.42). Conclusions—: CMBs in TIA and minor stroke are moderately common but do not predict recurrence or 90-day outcome. CAA-related transient focal neurological episodes and TIA have overlapping clinical symptoms, suggesting that MRI may be needed for differentiation. Abstract : Supplemental Digital Content is available in the text.